Screening of chilli microflora and other biocontrol agents for their antagonistic effects on spp. infecting chillies (The Journal of Plant Protection Sciences, 2020)
Forty-five leaf and nine fruit samples of chilli were collected from different regions of Karnataka for isolation of chilli microflora. From these samples, 94 fungal and 89 bacterial isolates were derived, which included 50 isolates of fungi and 44 isolates of bacteria from phylloplane and pomoplane, 44 isolates of endophytic fungi and 45 of endophytic bacteria from inside the leaf and fruit tissues, respectively. Among them, 70 fungal isolates belonged to plant pathogenic genera like, Alternaria, Cercospora, Colletotrichum, Curvularia, Glomerella,  Mycosphaerella,  Phoma  and  Stemphylium  and  the  other 24
Keywords: gloeosporioides; Glomerella; Mycosphaerella; Phoma Stemphylium